INOVASI LAYANAN DALAM UPAYA MEMBERIKAN LAYANAN PRIMA DI PERPUSTAKAAN UNIVERSITAS BENGKULU - Rahmawati, Nanik (Jurnal Perpustakaan dan Informasi, 2023)
ABSTRACT The purpose of this study to describe library innovation in an effort to provide excellent service to users at UPT Library Universitas Bengkulu This research uses qualitative descriptive research methods. The research subjects who became the source of data reference were the head of the library, librarians, and other staff in the library of Bengkulu University. Data collection techniques used are through interviews, observations, and document studies. Data analysis steps through data reduction, data presentation, and conclusion drawing or verification. The results of this study show that the criteria for the application of the management information system of the University of Bengkulu Library are using the SLiMS application (Senayan Library Management System) seen from all feasibility aspects both technically, operationally and economically feasible to be applied. According to the criteria of the management information system, the socialization and implementation of the system is good. This is evidenced by the results of data collection that has been carried out by the author from interviews, observations and documentation studies showing that the overall dimensions of management information system criteria have been very good in their application, because the management information system in the SLiMS application is available in the library, the Slims application menu feature is fairly easy to understand, and easily accessible. Before being implemented, pre-socialization has been held for the IT team as well as and librarians at Bengkulu University. The application of SLiMS is very helpful in efforts to effectively serve in libraries. In the application feature, the menu is adjusted to the needs in the library. The application of SLiMS plays an important role in improving the quality of learning and streamlining the performance of librarians. Evaluation of SLiMS applications is carried out continuously by obtaining feedback from users. The obstacles experienced are librarians who are accustomed to using manual systems and hardware limitations have found effective and efficient solutions. Based on the conclusions described above, suggestions for libraries that implement the SLiMS program are as follows; The Head of Library as a policy holder as well as an innovator must always strive to update technological developments and innovate, especially in terms of utilizing network-based institutional information systems so that they always become agile organizations. Network-based information systems applied in libraries must be evaluated in their application, evaluations carried out are not only limited to programs or applications that are being used but also include the entire hardware and internet network used by the institution. It is expected that the research conducted will be able to answer questions about service innovation at UPT Library of Bengkulu University and can be a reference for taking action or solution to the problem at hand. Keywords : Innovation – Service